Are firms as liquid as they appear in annual reports? - Khokhar, Abdul-Rahman; Qiu, Jiaping; Rahaman, Mohammad M.; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2022)
We find that firms report significantly higher cash holdings in the fourth fiscal quarter, followed by subsequent reversal. Such a phenomenon cannot be explained by traditional determinants of cash holdings, calendar year-end effect, or the choice of fiscal-year-end quarter. We identify real and timing apparatuses that firms employ to maneuver such a cash hike within a fiscal year. Furthermore, the fourth-quarter cash hike appears to be more pronounced for informationally opaque firms requiring frequent access to external capital markets and for firms with reduced external monitoring and lower financial constraints. Our results suggest that within-year cash-holding dynamics are important in fully assessing the liquidity and credit-risk situations of firms. Valuation Insight Measures of corporate cash holdings may be a misleading indicator of liquidity and value. The paper uncovers that firms tend to report higher cash holding in their final fiscal quarter, which are subsequently reversed. The reversal effect is stronger for more opaque firms that access external capital markets more often and for firms with less external monitoring and fewer financial constraints.
43 p. ; Includes bibliographical references (pp. 28-30)
Keywords: Cash hike; Cash holdings; Within-year cash dynamics; Marginal value of cash